On the influence of thought on language: a naturalistic framework for the pantomimic origins of human communication - Ferretti, Francesco (Frontiers in Psychology, 2023)
This paper focuses on the idea that pantomime is a privileged lens for investigating the origin of language in a naturalistic framework. Two reasons support this claim. The first one concerns the motivated and iconic character of pantomime compared to the arbitrary and abstract features of linguistic signs emphasized by the conventionalist thesis. The second reason is that a pantomimic account of language origin paves the way for a rethinking of the traditional hypothesis on the relationship between thought and language. Specifically, it leads to a revision of the thesis of the unidirectional influence of language on thought in favor of a bidirectional influence. Indeed, looking at the relationship between thought and language in its nascent stage means investigating the role of thought in shaping language rather than the role of language in shaping thought. A bidirectional perspective of this type hinges on the twofold idea that thought has primarily a narrative foundation and that pantomime represents an ideal expressive means for bootstrapping the evolutionary foundations of language origins in a naturalistic framework.